Research on the Formation Mechanism of Multiple Subjects’ Collaborative Governance in Chinese Old Urban Residential Area Renovation - Beibei Qin; Shuaijun Han; Yinan Li; Peifeng Wu (Buildings)
The renovation of old urban residential areas is and will continue to be an important part of urban renewal in China. The renovation of existing old urban residential areas focuses more on the physical level of renovation and pays insufficient attention to the improvement of collaborative community governance. However, collaborative community governance is the key to sustainable renovation. This study aims to explore the formation mechanism of multiple subjects’ collaborative governance in the renovation of old urban residential areas. A general collaborative governance theoretical framework was adopted and adjusted by innovatively introducing the improvement of collaborative community governance in old urban residential areas as an important variable in collaborative results. Data were collected through 853 questionnaires in 16 provinces across China and analyzed using Structural Equation Modeling. Data analysis reveals the following conclusions: (1) institution design and the collaborative process have significant positive impacts on collaborative results, while facilitative leadership has a negative impact; (2) the collaborative process is an important mediating variable on collaborative results; (3) government departments’ and residents’ self-governing organizations play important roles in improving collaborative community governance. Face-to-face dialogue and consultation, information disclosure and transparency, and reaching an intermediate consensus are important mediator variables. The research results provide theoretical support and practical suggestions for promoting the improvement of multiple-subject collaboration through old urban residential area renovation.